The Relationship Between Motor Skills, Social Problems, and ADHD Symptomatology: Does It Vary According to Parent and Teacher Report? - Goulardins, J.; Rigoli, Daniela; Loh, P.; Kane, R.; Licari, M.; Hands, B.; Oliveira, J.; Piek, J. (2015)
OBJECTIVE: This study investigated the relationship between motor performance; attentional, hyperactive, and impulsive symptoms; and social problems. Correlations between parents' versus teachers' ratings of social problems and ADHD symptomatology were also examined. METHOD: A total of 129 children aged 9 to 12 years were included. ADHD symptoms and social problems were identified based on Conners' Rating Scales-Revised: L, and the McCarron Assessment of Neuromuscular Development was used to assess motor skills. RESULTS: After controlling for ADHD symptomatology, motor skills remained a significant predictor of social problems in the teacher model but not in the parent model. After controlling for motor skills, inattentive (not hyperactive-impulsive) symptoms were a significant predictor of social problems in the parent model, whereas hyperactive-impulsive (not inattentive) symptoms were a significant predictor of social problems in the teacher model. CONCLUSION: The findings suggested that intervention strategies should consider the interaction between symptoms and environmental contexts.